Russian Banking Sector: Key Points of International Expansion - Panibratov, Andrei; Verbá, Cyril (Organizations and Markets in Emerging Economies, 2011)
Banking industry is traditionally seen as strictly regulated and driven to avoid political context. While Russian economy in general lacks both well developed regulatory framework and political independence of business entities, we would like to analyze the current state of affairs in an industry for which these attributes have become a hallmark. As Russian non-resource-based industries in general and the banking sector in particular are becoming more and more active players worldwide, the question arises, how exactly do Russian banks internationalize. We analyze four cases of international expansion by Russian banks in order to determine the main destinations for expansion, the entry modes used and whether they resemble resource-based companies in their internationalization. The results show that banks, even while being significantly state owned, are most likely guided by economic motives (as opposed to political ones), are leaning towards safer expansion destinations and are in several ways suffering from home market immaturity.